Integration of Financial Markets under the Conditions of the Eurasian Economic Union: Challenges and Opportunities - ISMAILOVA, Rymkul; MUSSINA, Amina; ABDIKARIMOVA, Aliya; OMARKHANOVA, Zhibek; NURGALIYEVA, Zhanna; ZHANGIROVA, Rimma (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The focus on the regional financial integration became a center of attention due to enhancement of cooperation among member states the Eurasian Economic Union and sustainable development. However, the reality of global experience demonstrated that such practices have ambiguous effects on economies. The article discloses main issues of the integration of financial markets in the framework of the Eurasian Economic Union through the analysis of preconditions and conditions of the formation of a single financial market. The research examined development of financial trade between Armenia, Belarus, Kazakhstan, Kyrgyzstan and Russia, creation of supranational bodies on regulation of the financial markets, formation of the developed financial infrastructure and favorable investment climate. The research based empirical study of statistical and secondary data of the member states, and conclusion and propositions on policies have been derived from the comparative analysis of the economies of these countries.